Teachers’ assessment of Chinese language syllabus at secondary schools in Malaysia - Peng, C.F.; Hoon, Y.C. (2014)
The study was conducted based on the conceptual framework of CIPP to evaluate teachers’ views on the Chinese Language Syllabus at lower secondary schools in Selangor state, Malaysia. The study involved 111 teachers from Chinese schools from different backgrounds. All sample subjects were randomly selected from ten districts of Selangor. Questionnaires were used as the research instruments and research questions used the Likert scale for measurement. The data were analyzed using SPSS. The results showed the continuation of syllabus from Form I to Form III, as well as consistency with the textbook contents. The findings also showed that teachers did not know clearly the three main domains in the syllabus and were unclear about the objective of the syllabus. Results of t-test and ANOVA test showed no significant differences in the evaluation of teachers in general despite the teachers’ different backgrounds. Teachers recommended that they should be given more opportunities in curriculum planning. In conclusion, the Chinese language syllabus is appropriate and the three main domains of interpersonal domain, information domain and maintenance of aesthetics domain should be simplified.